STUDIES ON THE CONSERVATION OF EPIDERMAL SPECIFICITIES OF SKIN AND CERTAIN MUCOSAS IN ADULT MAMMALS - Billingham, R. E. (The Rockefeller University Press, 1967)
To determine whether the factor(s) responsible for the conservation of epidermal specificities in adult guinea pigs and hamsters resides in the germinal layer of the epidermis or in the dermis, thin grafts of skin, possessing qualitatively distinct regional characteristics, were separated into their superficial epidermal and dermal components with the aid of trypsin. Dermis of one type was combined with epidermis of another to produce "recombinant" grafts which were then transplanted to small, full thickness cutaneous sites on the thorax of geneticaily compatible hosts. A variant of this procedure involved transplanting sheets of superficial epidermis of various types to shallow split thickness recipient areas in the skin of the thorax. All grafts were maintained for 100 days before they were excised and examined histologically. The results indicate that, whereas the dermis determines the kind of epidermis produced in recombinant grafts involving the ear, the sole of the foot, and the trunk, this is not the case in recombinants which include tongue, esophageal, or cheek pouch epithelia. The one exception to this occurred when tongue or esophagus epithelia were transplanted to split thickness beds in trunk skin. Here they appeared to produce an epidermis characteristic of their new location. It is believed that this exception is probably due to the fact that the native follicular epidermis present in trunk dermis made such a substantial contribution to the new superficial epidermis that it behaved overtly as body skin epidermis. Taken together, these results suggest that basal layer cells of the superficial epidermis of sole of foot skin, ear skin, and the hair-bearing skin of the general integument behave as if they are equipotential, and that in adult life maintenance of these particular epidermal specificities is the outcome of persistent specific inductive stimuli from the underlying dermis. The results of subsidiary experiments are reported which indicate that the epithelial component of mammary gland tissue is also pluripotential, being capable of producing, under appropriate conditions, a normal-looking, fully stratified superficial epidermis.